Insulinoma in the primary care: a case report - Teixeira, Delfim; Félix Tavares, Rita; Rodrigues, Alexandra; Moreira, Patrícia (International Surgery Journal, 2023)
Insulinoma is an uncommon neuroendocrine tumor that can cause unspecific signs and symptoms. In this case report is presented a 79-year-old man with a history of diabetes and alcohol abuse. He presented several episodes of hypoglycemia with associated symptoms. Considering the alcoholic habits and the fact that he did not take hypoglycemic medication, it was considered that the alcohol abuse was the most probable cause. However, hypoglycemia didn’t stop after he stopped drinking and the hypothesis of an insulinoma has occurred. He was referred to hospital consultation, but due to the COVID-19 pandemic, he lost follow-up for almost 2 years. He had new episodes of hypoglycemia and was hospitalized. A nodule in the uncinate process of the pancreas was detected on CT scan and he was subjected to an elective cephalic duodenopancreatectomy. Hypoglycemia can be a manifestation of several diseases. Insulinoma can mimic several pathologies, making it a challenging diagnosis. This case intends to report the importance of the family doctor in the diagnosis of pathologies with nonspecific signs and symptoms, as well as the orientation for secondary health care.